IbM KELOMPOK USAHA BATIK DI KELURAHAN SUTOREJO KOTA SURABAYA - Sumiati .; Yuliar Kartika; Siti Mujanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The purpose of this study is to develop of new Entrepreneur of the Housewives inSutorejo village, Surabaya Municipality, Indonesia. This study began by providingequipment and batik materials, than training of batik design and coloring as well asbusiness management so that the partners of this study becomes an entrepreneur, so thatcould generate additional income in the prosperous family. This activity is aimed athousewife in Sutorejo village, Mulyorejo Sub-district with name